Adaptation of a microbead assay for the easy evaluation of traditional anti-sickling medicines: application to DREPANOSTAT and FACA. (1st January 2018) - Villaret, Joran; Marti, Guillaume; Dubois, Frédérique; Reybier, Karine; Gaudre, Noémie; Haddad, Mohamed; Valentin, Alexis
Abstract: Context: Sickle cell disease is a common inherited blood disorder affecting millions of people worldwide. Due to lack of progress in drug discovery for a suitable treatment, sufferers often turn to traditional medicines that take advantage of the plant extracts activity used by traditional healers. Objective: This study optimizes an anti-sickling screening test to identify preparations capable of reverting sickle cells back to the morphology of normal red blood cells. We focused on the miniaturization and practicability of the assay, so that it can be adapted to the laboratory conditions commonly found in less developed countries. Materials and methods: We tested two traditional anti-sickling herbal medicines, FACA ® and DREPANOSTAT ®, composed of Zanthoxylum zanthoxyloides (Lam.) Zepern. & Timler (Rutaceae) and Calotropis procera (Aiton) Dryand. (Apocynaceae) at screening concentrations of hydroethanol extracts from 0.2 to 1 mg/mL. Potential bioactive molecules present in the extracts were profiled using Ultra High Performance Liquid Chromatography coupled with High Resolution Mass Spectrometry (UHPLC-HRMS/MS) method, identified through HRMS, MS/MS spectra and in silico fragmentation tools. Results: Hydroethanol extracts of FACA ® and DREPANOSTAT ® showed low anti-sickling activity, inhibiting less than 10% of the sickling process. The UHPLC-HRMS/MS profiles identified 28 compounds (18 in FACA ® and 15 in DREPANOSTAT ®, including common compounds) among which l -phenylalanine is already described as potential anti-sickling agent. When used as positive control, 7 mg/mL phenylalanine reduced the sickled RBC to 52%. Discussion and conclusions: This assay has been optimized for the easy screening of plant extracts or extracted compounds from bioassay guided fractionation, valuable to laboratories from less developed countries.